Impact of whey protein coating incorporated with Bifidobacterium and Lactobacillus on sliced ham properties - Pereira, Joana Odila (2018)
Edible coatings/films with functional ingredients may be a solution to consumers' demands for high-quality food products and an extended shelf-life. The aim of this work was to evaluate the antimicrobial efficiency of edible coatings incorporated with probiotics on sliced ham preservation. Coatings was developed based on whey protein isolates with incorporation of Bifidobacterium animalis Bb-12® or Lactobacillus casei-01. The physicochemical analyses showed that coating decreased water and weight loss on the ham. Furthermore, color analysis showed that coated sliced ham, exhibited no color change, comparatively to uncoated slices. The edible coatings incorporating the probiotic strains inhibited detectable growth of Staphylococcus spp., Pseudomonas spp., Enterobacteriaceae and yeasts/molds, at least, for 45 days of storage at 4 °C. The sensory evaluation demonstrated that there was a preference for the sliced coated ham. Probiotic bacteria viable cell numbers were maintained at ca. 108 CFU/g throughout storage time, enabling the slice of ham to act as a suitable carrier for the beneficial bacteria.